Changes in the Nucleotide Pool of Bacillus licheniformis During Sporulation - Leitzmann, Claus (1965)
Leitzmann, Claus (University of Minnesota, Minneapolis), and Robert W. Bernlohr. Changes in the nucleotide pool of Bacillus licheniformis during sporulation. J. Bacteriol. 89:1506–1510. 1965.—An analysis of the amount of acid-soluble nucleotides in Bacillus licheniformis cells showed a 75% increase during presporulation over that in log-phase cells. Cultures in which presporulation was inhibited by actinomycin D showed a decrease in acid-soluble nucleotides during the same time interval. A separation and quantitative determination of the nucleotides in the pool revealed that the relative proportion of each nucleotide remained fairly constant during presporulation. The detection of an intracellular ribonuclease activity and a decrease of the total nucleic acid concentration in the cells suggest that the increased pool arises from polymer breakdown. The effect of actinomycin D on sporulation was examined on both a quantitative and a temporal basis. The data indicate that messenger ribonucleic acid is essential for the completion of the sporulation process and must be resynthesized constantly.